RELIGIOUS INTERACTION AMONG THE AKOKO OF NIGERIA - Taiye Adamolekun (European Scientific Journal, ESJ, 2012)
This paper discusses Religious Interaction among the Akoko of Nigeria. The work explores Christian-Muslim relationin Akokoland and specifically examines why Christians and muslins have lived in peace since inception till date.The paper defines the Geographical location and the people of Akokoland. It discusses the advent of Islam and Christianity in Akoko. It examines the features of Islam and African Christianity.The paper highlights the facilitating factors, mode, and way of interaction. It gives suggestions and draws a conclusion.In our finding, it is discovered that in Akokoland, Muslims, Christians, and African religion live in absolute peace since the introduction of the religions into the area. The secret of this success is discovered to be hinged on mutual respect, accommodation, tolerance dialogue, and understanding among the religions in the area.